2022
DOI: 10.1186/s12957-022-02601-6
|View full text |Cite
|
Sign up to set email alerts
|

Four calcium signaling pathway-related genes were upregulated in microcystic adnexal carcinoma: transcriptome analysis and immunohistochemical validation

Abstract: Background Microcystic adnexal carcinoma (MAC) is a skin cancer with challenges in diagnosis and management. This study was aimed to detect molecular alterations of MAC and guide its pathologic diagnosis and treatment. Methods We performed transcriptome analysis on 5 MAC and 5 normal skin tissues, identified the differentially expressed genes, and verified them by immunohistochemistry. Results Three hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…6A). Among them, KEGG analysis further revealed that Atp2a1, Cacna1s, Casq1, Hrc, Ryr1, Tnnc2, Mylk2, Mylk4, and Trdn, which probably participate in regulating intracellular calcium concentration through the calcium signaling pathway to modulate pain sensitivity [50][51][52], might mediate the effect of ErbB4 on inflammatory pain sensation (Fig. 6F).…”
Section: Discussionmentioning
confidence: 99%
“…6A). Among them, KEGG analysis further revealed that Atp2a1, Cacna1s, Casq1, Hrc, Ryr1, Tnnc2, Mylk2, Mylk4, and Trdn, which probably participate in regulating intracellular calcium concentration through the calcium signaling pathway to modulate pain sensitivity [50][51][52], might mediate the effect of ErbB4 on inflammatory pain sensation (Fig. 6F).…”
Section: Discussionmentioning
confidence: 99%
“…The Food and Drug Administration has authorized one for subgroups of breast cancer patients[ 13 , 14 ]. Yu et al [ 15 ] investigated four calcium signaling pathway genes, including CACNA1S, RYR1, ATP2A1, and MYLK3, that were elevated in MAC at the RNA level and expressed more in MAC than in normal sweat glands and histologic mimics of MAC at the protein level. C-kit has been found in a subgroup of MAC patients, boosting the prospect of future use of imatinib mesylate.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al [52] found potential for therapeutic targeting of p53 or the JAK/STAT pathway in advanced microcystic adnexal carcinomas. Yu et al [53] addressed four genes of the calcium signaling pathway as upregulated in microcystic adnexal carcinomas at both RNA and protein levels suggesting that CACNA1S, ATP2A1, RYR1, and MYLK3 may be new diagnostic molecular markers and therapeutic targets in these rare neoplasms.…”
Section: Treatmentmentioning
confidence: 99%